Mobility management incorporating fuzzy logic for heterogeneous a IP environment. - Chan, P.M.L.
The next generation in mobility management will enable different mobile networks to interoperate with each other to ensure terminal and personal mobility and global portability of network services. However, in order to ensure global mobility, the deployment and integration of both satellite and terrestrial components are necessary. This article is focused on issues related to mobility management in a future mobile communications system, in a scenario where a multisegment access network is integrated into an IP core network by exploiting the principles of Mobile IP. In particular, attention is given to the requirements for location, address, and handover management. In a heterogeneous environment, the need to perform handover between access networks imposes particular constraints on the type of information available to the terminal and network. In this case, consideration will need to be given to parameters other than radio characteristics, such as achievable quality of service and user preference. This article proposes a new approach to handover management by applying the fuzzy logic concept to a heterogeneous environment. The article concludes with a presentation of mobility management signaling protocols
Keywords: IP core network; Mobile IP; Address management; Future mobile communications system; Fuzzy logic; Global mobility; Global portability; Handover management; Heterogeneous IP environment; Heterogeneous environment; Location management; Mobility management; Mobility management signaling protocols; Multisegment access network; Personal mobility; Quality of service; Satellite components; Terminal mobility; Terrestrial components; User preference